Torsional effects in strong-field ionization of molecules - Andrey I. Dnestryan; Oleg I. Tolstikhin; Frank Jensen; Lars Bojer Madsen (Physical Review Research, 2019)
We investigate how the ionization rate of molecules consisting of a pair of phenyl rings depends on the torsional dihedral angle between these two rings. We consider different orientations of the molecules with respect to the external field direction and find differences in the rates in biphenyl and substituted biphenyl. The evaluation of the rates is made possible by application of the integral representation of the weak-field asymptotic theory for tunneling ionization. We report a strong variation of the ionization rates with dihedral angle with contributions from several orbitals and a large difference between biphenyl and substituted biphenyl related to the permanent dipole of the latter system.